Negative heterosis for meiotic recombination rate in spermatocytes of the domestic chicken Gallus gallus - L. P. Malinovskaya; K. V. Tishakova; T. I. Bikchurina; A. Yu. Slobodchikova; N. Yu. Torgunakov; A. A. Torgasheva; Y. A. Tsepilov; N. A. Volkova; P. M. Borodin (Вавиловский журнал генетики и селекции)
Benefits and costs of meiotic recombination are a matter of discussion. Because recombination breaks allele combinations already tested by natural selection and generates new ones of unpredictable fitness, a high recombination rate is generally beneficial for the populations living in a fluctuating or a rapidly changing environment and costly in a stable environment. Besides genetic benefits and costs, there are cytological effects of recombination, both positive and negative. Recombination is necessary for chromosome synapsis and segregation. However, it involves a massive generation of double-strand DNA breaks, erroneous repair of which may lead to germ cell death or various mutations and chromosome rearrangements. Thus, the benefits of recombination (generation of new allele combinations) would prevail over its costs (occurrence of deleterious mutations) as long as the population remains sufficiently heterogeneous. Using immunolocalization of MLH1, a mismatch repair protein, at the synaptonemal complexes, we examined the number and distribution of recombination nodules in spermatocytes of two chicken breeds with high (Pervomai) and low (Russian Crested) recombination rates and their F1 hybrids and backcrosses. We detected negative heterosis for recombination rate in the F1 hybrids. Backcrosses to the Pervomai breed were rather homogenous and showed an intermediate recombination rate. The differences in overall recombination rate between the breeds, hybrids and backcrosses were mainly determined by the differences in the crossing over number in the seven largest macrochromosomes. The decrease in recombination rate in F1 is probably determined by difficulties in homology matching between the DNA sequences of genetically divergent breeds. The suppression of recombination in the hybrids may impede gene flow between parapatric populations and therefore accelerate their genetic divergence.